2020
DOI: 10.1108/josm-05-2020-0140
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social distancing on employee well-being: a conceptual framework and research agenda

Abstract: PurposeThe ongoing pandemic caused by the coronavirus disease 2019 (COVID-19) virus has severely influenced lives and livelihoods. As service organizations either face hibernation or continuity of their business operations, the impact of social distancing measures raises major concerns for the well-being of service employees. In this paper, the authors develop a conceptual framework to examine how different social distancing practices impact an organization's service continuity or service hibernation, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
158
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 40 publications
2
158
0
1
Order By: Relevance
“…Initially, travel restrictions between certain countries and advisory measures like work from home to promote social distancing are applied. However, they realized that the virus had already spread, and many governments switched to mandatory restrictions like lockdowns and travel bans ( Tuzovic and Kabadayi, 2020 ). In another study, Tsionas (2020) discussed the problem of post-COVID-19 gradual adjustment in the tourism and hospitality industry.…”
Section: Literature Revie Wmentioning
confidence: 99%
“…Initially, travel restrictions between certain countries and advisory measures like work from home to promote social distancing are applied. However, they realized that the virus had already spread, and many governments switched to mandatory restrictions like lockdowns and travel bans ( Tuzovic and Kabadayi, 2020 ). In another study, Tsionas (2020) discussed the problem of post-COVID-19 gradual adjustment in the tourism and hospitality industry.…”
Section: Literature Revie Wmentioning
confidence: 99%
“…In the absence of a COVID-19 vaccine, countries worldwide implemented social distancing (Tuzovic and Kabadayi, 2020) measures to prevent the spread of the contagious and even lethal virus. However, social distancing, conceivably resulting in social isolation, is in stark contrast with the deep-rooted human instinct to connect with others and therefore resulting in feelings of loneliness (Bavel et al, 2020).…”
mentioning
confidence: 99%
“…Organizations and their management must understand how employees view personal and family FWB and offer financial planning training and services to employees to help them and their families cope with economic uncertainties and manage their stress. It is particularly essential in light of the current COVID-19 pandemic, which has hit the global economy and people's livelihoods in an unprecedented scale and manner, even though governments all over the world have implemented economic simulation packages and income protection schemes (Brewer & Gardiner, 2020;Tuzovic & Kabadayi, 2020). Tuzovic and Kabadayi (2020) suggested that while social and financial supports from governments can offer relief in financial difficulties for those employees who lose their jobs in the short-term, the prolonged COVID-19 will inevitably adversely affect employee well-being including FWB significantly.…”
Section: Practical Implicationsmentioning
confidence: 99%